Recombinational repair of radiation-induced double-strand breaks occurs in the absence of extensive resection - Westmoreland, James W. (Nucleic Acids Res, 2016)
Recombinational repair provides accurate chromosomal restitution after double-strand break (DSB) induction. While all DSB recombination repair models include 5′-3′ resection, there are no studies that directly assess the resection needed for repair between sister chromatids in G-2 arrested cells of random, radiation-induced ‘dirty’ DSBs. Using our Pulse Field Gel Electrophoresis-shift approach, we determined resection at IR-DSBs in WT and mutants lacking exonuclease1 or Sgs1 helicase. Lack of either reduced resection length by half, without decreased DSB repair or survival. In the exo1Δ sgs1Δ double mutant, resection was barely detectable, yet it only took an additional hour to achieve a level of repair comparable to WT and there was only a 2-fold dose-modifying effect on survival. Results with a Dnl4 deletion strain showed that remaining repair was not due to endjoining. Thus, similar to what has been shown for a single, clean HO-induced DSB, a severe reduction in resection tract length has only a modest effect on repair of multiple, dirty DSBs in G2-arrested cells. Significantly, this study provides the first opportunity to directly relate resection length at DSBs to the capability for global recombination repair between sister chromatids.